The Relationship of Students' Perceptions Regarding the Implementation of Industry-Based Teaching Factory on the Skills of Class XI Culinary Students of SMKN 1 Lembah Gumanti - Wirhamni Wirhamni; Ezi Anggraini; Asmar Yulastri; Wiwik Indrayeni (Educia Journal, 2026)
This research was motivated by the sub-optimal implementation of the industry-based Teaching Factory in improving the skills of culinary skills program students at Vocational High Schools (SMK). This research aims to determine the relationship between students' perceptions regarding the implementation of industry-based Teaching Factory and the culinary skills of class XI SMKN 1 Lembah Gumanti. The research uses a quantitative approach with ex post facto correlational research. The research population consisted of 50 class XI students of the culinary skills program, with a sampling technique using total sampling, so that the entire population was used as the research sample. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data analysis includes descriptive statistics, normality test, linearity test, Pearson correlation test, simple linear regression analysis, and coefficient of determination. The research results show that the data is normally distributed and has a linear relationship. The results of the Pearson correlation test show that there is a significant relationship between students' perceptions of the implementation of industry-based Teaching Factory and students' culinary skills (r = 0.295; p = 0.038 < 0.05). Regression analysis produces the equation Y = 62.527 + 0.364 Thus, it can be concluded that students' perceptions of the implementation of industry-based Teaching Factory have a positive and significant relationship to the culinary skills of class XI SMKN 1 Lembah Gumanti, although the level of relationship is relatively low.